Factors influencing consumer electronic word-of-mouth intention among Gen-Y towards travel destination / Muhammad Ikram Badrul Hisham - Badrul Hisham, Muhammad Ikram (Faculty of Business and Management, 2018)
This research purpose is to study the factor influencing consumers’ eWOM intention among generation Y towards travel destination. Electronic word-of-mouth (eWOM) have received significant attention in recent years which could influence the purchasing decisions of consumers. Thus, eWOM can happen in an online communities such as communities of practice and online communities of interest. However, there is lack of understanding of motivation of consumers for exchanging information and knowledge online. EWOM can be seen in online consumers platforms such as consumer reviews websites, blogs, forum and social media sites, travel communities and many more. For example, tourists will search for information at TripAdvisor about a place they want to visit before making a purchasing decision. Therefore, this research will be focus on the population of generation Y and 101 sets of questionnaire was distributed in order to measure the data. This study also shows that 55.4% of the variance which includes egoism, collectivism, enjoyment of helping and moral obligation is significantly related to consumers’ eWOM intention. The results from this study shows that enjoyment of helping is the strongest factor that influence consumers’ eWOM intention.